2021
DOI: 10.4103/jips.jips_91_21
|View full text |Cite
|
Sign up to set email alerts
|

Retention of different CAD/CAM endocrowns bonded to severely damaged endodontically treated teeth: An in vitro study

Abstract: Aim: Assess the retention of endocrowns fabricated of different CAD/CAM materials. Settings and Design: In vitro - comparative study. Material and Methods: Root canal treated mandibular first molars were prepared in a standardized method. Standardized endocrowns were manufactured using four CAD-CAM blocks: resin infiltrated ceramic (Vita Enamic), partially stabilized tetragonal zirconia (Katana), lithium disilicate ceramic (IPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
(42 reference statements)
0
5
0
1
Order By: Relevance
“…Endocrowns can be fabricated by CAD/CAM or heat-press techniques using various ceramic systems, such as lithium silicates and zirconia-reinforced lithium silicates [ 14 , 48 , 49 ]. A variety of the products are used in dental practice and produce prostheses with better accuracy of marginal variation [ 13 , 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endocrowns can be fabricated by CAD/CAM or heat-press techniques using various ceramic systems, such as lithium silicates and zirconia-reinforced lithium silicates [ 14 , 48 , 49 ]. A variety of the products are used in dental practice and produce prostheses with better accuracy of marginal variation [ 13 , 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, publications such as the one by Yasmin Elashmawy et al appeared, which evaluated the retention of endocrowns made of different materials. The results showed that lithium disilicate glass ceramics and resin-infiltrated ceramics recorded considerably higher retention values, while the use of zirconia obtained a favorable failure that avoided possible tooth fracture [9].…”
Section: Literature Reviewmentioning
confidence: 98%
“…Vita Enamic та IPS e.max CAD продемонстрували набагато кращу ретенцію, ніж реставрації з Katana та PEEK. Під час дебондингу Vita Enamic та IPS e.max CAD були з'єднані зі зламаними сегментами зуба, тоді як зразки Katana та PEEK були відірвані за лінією адгезії [14].…”
Section: рис 1 стратегія пошуку наукових джерелunclassified